2015
DOI: 10.3109/15412555.2015.1043523
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Positive Expiratory Pressure in Chronic Obstructive Pulmonary Disease

Abstract: Evidence-based guidance for the use of airway clearance techniques (ACT) in chronic obstructive pulmonary disease (COPD) is lacking in-part because well-established measurements of pulmonary function such as the forced expiratory volume in 1s (FEV1) are relatively insensitive to ACT. The objective of this crossover study was to evaluate daily use of an oscillatory positive expiratory pressure (oPEP) device for 21-28 days in COPD patients who were self-identified as sputum-producers or non-sputum-producers. COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…Despite the availability of a range of therapy options, exacerbations continue to be a common cause of healthcare resource use among COPD patients [14]. The mechanisms for protection from symptomatic exacerbations are not well understood, but improved sputum clearance, reduced variability in airway smooth muscle tone, and increased dyspnea thresholds are possible explanations [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of a range of therapy options, exacerbations continue to be a common cause of healthcare resource use among COPD patients [14]. The mechanisms for protection from symptomatic exacerbations are not well understood, but improved sputum clearance, reduced variability in airway smooth muscle tone, and increased dyspnea thresholds are possible explanations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobika (TMI, London, ON) is a handheld mechanical OPEP device where patients exhale against a manually adjusted variable resistance. Aerobika has been shown to significantly improve forced vital capacity (FVC), 6-min walk distance (6MWD), and St. George's Respiratory Questionnaire (SGRQ) score in COPD patients [14]. However, the effectiveness of an OPEP device, such as Aerobika, in reducing the COPD exacerbations has not been studied in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the Aerobika OPEP device resulted in a direct medical cost savings of $553 per patient [20]. These data suggest that the reductions in healthcare resource use and costs associated with the Aerobika OPEP device among postoperative patients in our study may result from the beneficial effects of this device on improving airway structure and function [16,17], thus reducing the risk of developing a PPC that warrants rehospitalization.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical trial results have demonstrated that use of the Aerobika OPEP device significantly improves dyspnea, quality of life, exercise capacity and ease in bringing up sputum in patients with COPD and bronchiectasis [16]. In another clinical trial, the Aerobika OPEP device was further shown to significantly improve ventilation in patients with COPD [17]. In addition, real-world evidence suggests that the use of the Aerobika OPEP device among COPD patients significantly reduces exacerbations by nearly 30% [18].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the authors illustrate yet another important consideration, which is to introduce the concept of minimally important clinical differences in follow-up measurements (11). Although establishing minimally important clinical differences is beyond the scope of one study, the team instead used previously analyzed results of inter-visit variance to establish a smallest detectable difference (12). This value is remarkably small considering the comparable variability of PFT metrics such as FEV 1 is around 6% (13).…”
mentioning
confidence: 99%